A new robotically assisted system for total knee arthroplasty: A sheep model study. Issue 4 (25th April 2021) - Chen, Xin; Li, Zheng; Zhang, Xiaofeng; Yan, Jun; Ding, Lele; Song, Youdong; Huo, Yujia; Chan, Matthew T.V.; Wu, William K.K.; Lin, Jin
Abstract: Background: We investigated the accuracy and safety of a new HURWA robotic‐assisted total knee arthroplasty (TKA) system in a sheep model. Methods: Ten male small‐tailed Han sheep were used in this study. Sheep were imaged by computed tomography scan before and after bone resection and the cutting errors between actual bone preparation and preoperative planning of the femur and tibia in three dimensions were measured. Results: The overall accuracies after surgery compared with that from preoperative surgical planning of the left and right femurs were 1.93 ± 1.02° and 1.93 ± 1.23°, respectively. Additionally, similarly high overall accuracies for the left and right tibia of 1.26 ± 1.04 and 1.68 ± 0.92°, respectively, were obtained. The gap distances of the distal cut, anterior chamfer, anterior cut, posterior chamfer and posterior cut on the medial side were 0.47 ± 0.35 mm, 0.41 ± 0.37 mm, 0.12 ± 0.26 mm, 0.41 ± 0.44 mm and 0.12 ± 0.23 mm, respectively. No intraoperative complications, such as intraoperative fracture, massive bleeding or death, occurred. Conclusion: This new HURWA robotic‐assisted TKA system is an accurate and safe tool for TKA surgery based on the sheep model.